Optimizing The Growth of Corn Plant (Zea mays L) Local Variety of North Sumatera, which has been Irradiated with Gamma-Rays M1 with Urea Fertilizer Application - Musthofa, Nurul; Mustamu, Novilda Elizabeth; Sitanggang, Kamsia Dorliana; Triyanto, Yudi (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Corn (Zea mays L.) is the second most important food crop after rice and is a cereal crop that grows in various regions worldwide. Local varieties of corn in North Sumatra require high nutrient levels for optimal cultivation, particularly nitrogen (N), which is commonly supplied through urea fertilizer. The high demand for nitrogen in urea often leads farmers to apply it in inappropriate doses, resulting in several agronomic issues. This study aims to evaluate the growth of local varieties of corn in North Sumatra in response to different doses of urea fertilizer. The research was conducted in the experimental field in Perbaungan Village, Hulu Bilah District, Labuhanbatu Regency, North Sumatra, from December 2024 to February 2025. A Non-Factorial Completely Randomized Design (CRD) was employed, consisting of five treatment levels, each repeated four times. The urea fertilizer doses applied were as follows: control (no treatment), 2 g/polybag, 4 g/polybag, 6 g/polybag, and 8 g/polybag. The results indicate that varying doses of urea fertilizer significantly influence the growth of local North Sumatra corn plants, particularly in plant height and stem diameter. The optimal dose of urea fertilizer for promoting the development of these corn plants is determined to be 4 g/polybag.